LOYALTY ASSESSMENT OF COMPANY COSTUMER WITH CLASSIFICATION METHOD - Fricles Ariwisanto Sianturi; Jonson Manurung; R.Fanry Siahaan (INFOKUM, 2020)
Companies in general want the customers they have to be able to sustain forever. To make this happen is not something that is easy in the current climate of intense business competition, considering that there are rapid changes that can occur at any time, such as changes in customers, competitors and changes in broad conditions that are always dynamic. This requires policy makers to develop a strategy capable of achieving sales growth targets, increasing the company's market share. For this reason, an analysis of customer loyalty is needed. For this reason, an analysis is needed to understand and assess customer loyalty using a classification design method. With classification, information can be produced more quickly and the information presented is analytical in nature so that it is easy to use for decision making.